2021
DOI: 10.3390/ijms222212193
|View full text |Cite
|
Sign up to set email alerts
|

Metals in ALS TDP-43 Pathology

Abstract: Amyotrophic lateral sclerosis (ALS), Alzheimer’s disease, Parkinson’s disease and similar neurodegenerative disorders take their toll on patients, caregivers and society. A common denominator for these disorders is the accumulation of aggregated proteins in nerve cells, yet the triggers for these aggregation processes are currently unknown. In ALS, protein aggregation has been described for the SOD1, C9orf72, FUS and TDP-43 proteins. The latter is a nuclear protein normally binding to both DNA and RNA, contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 140 publications
1
10
0
Order By: Relevance
“…Metal-binding irregularities play a role in diseases such as Alzheimer's [13,14], ALS [15] and neurodegenerative disorders [6], among many others. Nickel and the essential metal, cobalt, are among the metals that can cause allergic reactions in humans [16].…”
Section: Metal Binding In Biological Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Metal-binding irregularities play a role in diseases such as Alzheimer's [13,14], ALS [15] and neurodegenerative disorders [6], among many others. Nickel and the essential metal, cobalt, are among the metals that can cause allergic reactions in humans [16].…”
Section: Metal Binding In Biological Systemsmentioning
confidence: 99%
“…Paramagnetic probes can be introduced into the molecule by performing two experiments in which the Ca(II) ion is exchanged, respectively by different lanthanides that have dissimilar magnetic susceptibility anisotropy tensors, such as Tb(III) or Tm(III): Internuclear vectors referenced to each lanthanide provide additional information regarding internal orientation relative to the paramagnetic probe [109,110]. The relative dynamic motion of the bound and apo structures of calmodulin can be measured by 1 H- 15 N transverse relaxation optimized spectroscopy-heteronuclear single quantum coherence (TROSY-HSQC) experiments [111].…”
Section: Calciummentioning
confidence: 99%
See 2 more Smart Citations
“…Many facts and mechanisms may be involved in this process, as epidemiological studies suggest a relationship between environmental exposure to metals and the risk of PD, as it has been observed that disorders with brain-metal accumulation may manifest with parkinsonism; in animal studies, the effects of chelation treatment were detected, and measurements of metal concentrations and metal regulatory protein expression in cerebrospinal fluid and post-mortem brain-tissue samples [32]. ALS pathology also appears to include metal imbalances, and a known risk factor for ALS can be environmental-metal exposure [33]. It has been proven that administration of a Cu-chelating agent (ammonium tetrathiomolybdate) enhanced survival and slowed ALS progression [34].There is accumulating evidence that exercise can enhance brain function and attenuate neurodegeneration in such mechanisms as improving neuroplasticity by altering the synaptic structure and function in many brain regions.…”
Section: Introductionmentioning
confidence: 99%